Flexor Tendon Rupture Following Collagenase Clostridium histolyticum Versus Percutaneous Needle Fasciotomy in the Management of Dupuytren’s Disease: A Systematic Review and Meta-Analysis - Sherlyn Chng; Omar Shadid; Ishith Seth; Warren Rozen (Journal of Personalized Medicine, 2026)
Background: Flexor tendon rupture is a rare but potentially disabling complication following minimally invasive treatment of Dupuytren’s disease. This meta-analysis compared rupture incidence after collagenase Clostridium histolyticum (CCH) injection and percutaneous needle fasciotomy/aponeurotomy (PNF/PNA). Methods: PubMed, MEDLINE, and Embase were systematically searched for randomised trials, cohort studies, clinical trials, and case series reporting complications after CCH or PNF for Dupuytren’s disease. Case reports and secondary evidence were excluded from incidence calculations, although reference lists of reviews were screened for eligible primary studies. Flexor tendon rupture events and study denominators were extracted as reported. Pooled incidence was estimated using random-effects proportional meta-analysis with logit transformation and continuity correction. Separate pooled estimates were generated for CCH and PNF, followed by subgroup comparison. Results: Forty-one studies were included. Across eligible studies, 68 flexor tendon ruptures were identified, including 62 after CCH and 6 after PNF. Ruptures most commonly involved the flexor digitorum profundus, affected the small finger, and occurred early, with a median time to rupture of 8 days, where reported. Fourteen PNF cohorts comprising 6058 treated units reported 6 ruptures, producing a pooled incidence of 0.32% (95% CI: 0.18–0.55%) with no observed heterogeneity. Twenty-nine CCH cohorts comprising 60,949 treated units reported 62 ruptures, producing a pooled incidence of 0.83% (95% CI: 0.42–1.64%) with substantial heterogeneity. Subgroup comparison demonstrated a higher pooled rupture incidence following CCH than PNF. Conclusions: Flexor tendon rupture is uncommon after both CCH and PNF. Characterisation of anatomical and treatment-related patterns of rupture may support more individualised risk counselling and treatment selection in Dupuytren’s disease. Future studies are required to develop clinically meaningful risk-stratification strategies.